Perspectives on food traceability system: A case in chain restaurant franchising - Jun-Zhi Chiu; Chao-Chen Hsieh (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
Traceability has become increasingly important in Taiwan. The global food supply chain today has evolved into a tangled web as companies seek to enhance their capabilities to fulfill customers' needs. Food traceability system (FTS) can reduce information asymmetry in chain restaurants' food safety issues. This study used focus group to explore the information requirements of chain restaurants food safety system. The selection of four participants was divided in two groups i.e. external traceability and internal traceability group. External traceability captured and shared critical food ingredients of e-traceability with upstream and downstream chain partners. Additionally, FTS timely provides backward trace of ingredients information to supplier's supplier and forward ingredients information to customer's customer. Internal traceability refers to the raw materials or products of each batch in the food chain. The promotion of technology development and application of the value to establish their own external and internal traceability considerations include the origins of food including the practices related to food labeling, food hygiene, food additives and pesticide residues, as well as guidelines for the management of traceability. Through FTS movements can be traced one step backwards and one step forward at any point in the supply chain governmental import and export inspection and certification systems for foods.
Keywords: L66; L86; 330; Chain restaurant franchising; food traceability; external traceability; internal traceability; focus group